Clinico-histopathological Correlation in Ectopic Pregnancy: Insights from a Rural Tertiary Center in Maharashtra, India (GAIMS Journal of Medical Sciences, 2025)
Background: Derived from the Greek word ektopus, meaning "out of place," ectopic pregnancy entails the implantation of conceptus in any site other than a normal uterine location.[1] It remains a formidable challenge in women's healthcare, posing risks to both maternal life [2] and future fertility with global incidence ranging from 1-2%,[3] with approximately 3.12 per 1000 pregnancies in India. This study endeavors to conduct a comprehensive analysis of ectopic pregnancy cases, underscoring the pivotal role of histopathological examination in not only confirming the diagnosis but also unraveling the underlying etiologies. By integrating clinical findings with pathology, we aim to improve diagnostic accuracy, enabling timely interventions, fertility preservation, and better patient outcomes.Material and methods: A retrospective analysis was conducted on 120 cases of ectopic pregnancy diagnosed between January 2021 and January 2024 at the Department of Pathology, Swami Ramanand Teerth Rural Government Medical College, Ambajogai. Clinical data, including age, parity, gestational age, and risk factors, were collected. Histopathological specimens were processed and examined using Hematoxylin and Eosin (H&E) staining, with detailed observations recorded and analyzed.Results: The incidence of ectopic pregnancy was 1.13% of all gynecological cases, with the majority (70.83%) of patients in the 21-30 years age group. Multigravidity was common, with 47.12% presenting during their second pregnancy. The fallopian tube was the most frequent implantation site (97.29%), and rupture occurred in 57.65% of cases. Histopathological findings included chronic salpingitis (56.48%), salpingitis isthmica nodosa (9.2%), and acute salpingitis (4.6%). Additionally, 16.66% of cases were classified as normal.Conclusion: Histopathological examination is essential for the accurate diagnosis and management of ectopic pregnancies, particularly in atypical cases. The integration of clinical and pathological data enhances diagnostic precision, aids in identifying complications, and informs future fertility management. This study highlights the importance of clinicopathological correlation in ensuring optimal patient care and outcomes in ectopic pregnancy cases.